The Function and Usage of Articles in English - Muhammadova Sitorabonu San'atjon qizi (Web of Journals Publishing, 2023)
The primary objective of this article is to emphasize and highlight the significant role of articles in the English language, while also providing a comprehensive understanding of their usage and importance in variuos linguistic contexts.
Keywords: article, language, noun, singular, countable, definite, indefinite, common, proper noun, names, vowel, consonant.